The parallax view - Zizek, Slavoj (Cambridge, Massachusetts The MIT Press, 2006)
"A parallax can be defined as the apparent displacement of an object caused by a change in observational position. Author Slavoj Zizek is interested in the "parallax gap" separating two points between which no synthesis or mediation is possible, linked by an "impossible short circuit" of levels that can never meet. From this consideration of parallax, Zizek begins a rehabilitation of dialectical materialism. The Parallax View not only expands Zizek's Lacanian-Hegelian approach to new domains (notably cognitive brain sciences) but also provides the systematic exposition of the conceptual framework that underlies his entire work."--Jacket.
Introduction : Dialectical materialism at the gates. -- The stellar parallax : the traps of ontological difference : The subject, this "inwardly circumcised Jew" -- Building blocks for a materialist theology. -- Interlude 1 : Kate's choice, or, the materialism of Henry James. -- The solar parallax : the unbearable lightness of being no one : The unbearable heaviness of being divine shit. -- Interlude 2 : Objet petit a in social links, or, the impasse of anti-anti-semitism. -- The lunar parallax : toward a politics of subtraction : From surplus-value to surplus-power -- The obscene knot of ideology, and how to untie it.
Photocopy.
Includes bibliographical references (leaves 387-429) and index.
Keywords: Philosophy